(3bUe GdeHOYjf HSfGf GdSfIs
(3ChdgG (B:s
(3MeOkG def QaY CdhjI GdChdjGA ai LejY GdbQhf CeG HYO aEf HYV CHfGA GdReGf deG eQhG GeQGQkG ai WQb GdWZjGf s
(3BNQgG (B:s
(3bdJ COY di abGd jG Mi jG bjhe jBgjG TQG MjG Ke bdJ ce ef GdCfHjGA ai GdMjGI bGd CfG hGdNVQ hEOQjS hYjSi bdJ gd JdJbi CfG hGdNVQ bGd fYe ai cd YGe HYQaGJ hUdi Gddg Ydi eMeO hBdg CLeYjf hYdi SGFQ GdCfHjGA hGdeQSdjf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B35s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeLGejYs